PELATIHAN PEMBUATAN PUPUK CAIR DARI LIMBAH AIR KOLAM IKAN UNTUK PERTANIAN TERPADU DI DESA BUNUTIN - Ni Putu Anglila Amaral; Nyoman Yudiarini; Susanti Rambu Sori; Dionisius Savio Batas; I Gusti Lanang Ag. Jelantik Dwija (Universitas Mataram, 2026)
The transformation of fish pond wastewater into liquid fertilizer can be regarded as a strategic innovation to support the sustainability of integrated agriculture–aquaculture systems in rural areas. This community service program was implemented in Bunutin Village, Bangli District, to enhance farmers’ knowledge and skills in producing organic liquid fertilizer from fishpond effluents, particularly from catfish and tilapia cultivation. Fishpond wastewater contains valuable nutrients such as nitrogen, phosphorus, and potassium, which, if properly processed through fermentation with microbial activators, can serve as an effective and environmentally friendly fertilizer. The training program involved socialization, hands-on demonstrations, and mentoring sessions attended by farmer groups who combine aquaculture with rice and horticultural crop cultivation. The activities included introducing nutrient content in fish wastewater, practical methods for filtering, mixing with molasses and EM4, and fermentation processes lasting 7–14 days. Participants also applied the fertilizer to horticultural crops such as tomatoes and chilies to evaluate its effectiveness. Evaluation through pre- and post-tests revealed a significant increase in participants’ knowledge and skills, with understanding of fertilizer-making techniques rising from limited awareness to more than 70% proficiency. The program demonstrated that liquid fertilizer derived from fish wastewater not only reduces dependence on chemical fertilizers and lowers production costs but also contributes to sustainable farming practices and environmental preservation. Furthermore, this initiative strengthens local food security by promoting circular agriculture, where aquaculture by-products become valuable inputs for crop production. Overall, the training has empowered farmers to independently produce liquid fertilizer, encouraged group-based production, and opened opportunities for developing eco-friendly local products with market potential.